2000
DOI: 10.1055/s-2000-8531
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Allergic and Anti-Inflammatory Triterpenes from the Herb of Prunella vulgaris

Abstract: The activity-guided fractionation of the extract of the herb of Prunella vulgaris (Labiatae) led to the isolation of four triterpenes, i.e., betulinic acid, ursolic acid, 2 alpha,3 alpha-dihydroxyurs-12-en-28-oic acid, and 2 alpha-hydroxyursolic acid. One of these compounds, 2 alpha,3 alpha-dihydroxyursolic acid, demonstrated significant inhibition on the release of beta-hexosaminidase from the cultured RBL-2H3 cells in a dose-dependent manner; the IC50 value was calculated to be 57 microM. When the isolated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
122
1
5

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(137 citation statements)
references
References 3 publications
3
122
1
5
Order By: Relevance
“…Previous phytochemical studies on the biologically active components of P. vulgaris have been isolated and reported to mainly contain triterpenoids, phenolics, flavonoids, tannins, caffeic acids, and anionic polysaccharide prunelline (Ryu et al, 2000;Wang et al, 2000;Jiang et al, 2008). Rosmarinic acid (RA), one of the major phenolics, suppresses lipoperoxidation (Laranjinha et al, 1994), scavenges superoxide radicals (Osakabe et al, 2002), and exhibits anti-inflammatory (Osakabe et al, 2004) and antioxidant (Psotova et al, 2003) bioactivity.…”
Section: Introductionmentioning
confidence: 99%
“…Previous phytochemical studies on the biologically active components of P. vulgaris have been isolated and reported to mainly contain triterpenoids, phenolics, flavonoids, tannins, caffeic acids, and anionic polysaccharide prunelline (Ryu et al, 2000;Wang et al, 2000;Jiang et al, 2008). Rosmarinic acid (RA), one of the major phenolics, suppresses lipoperoxidation (Laranjinha et al, 1994), scavenges superoxide radicals (Osakabe et al, 2002), and exhibits anti-inflammatory (Osakabe et al, 2004) and antioxidant (Psotova et al, 2003) bioactivity.…”
Section: Introductionmentioning
confidence: 99%
“…Triterpenoids are almost ubiquitous in plants and have long been considered to be the antiinfl ammatory principles of several drugs, particularly in the form of triterpene glycosides. The reported biological effects of triterpenoids include cytotoxic, antitumor, antiinfl ammatory and antiviral activities (Recio et al, 1995;Fulda and Debatin, 2000;Ryu et al, 2000). In 1995, betulinic acid was reported to be a selective inhibitor of human melanoma (Pisha et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…lilacina ameliorated drug-induced memory dysfunction (Park et al, 2010) and showed anti-allergic and anti-inflammatory activity (Ryu et al, 2000;Psotová et al, 2003). Previous studies indicated that the Prunella vulgaris var.…”
Section: Discussionmentioning
confidence: 99%
“…lilacina is one of the most widely used medical plants in north-eastern Asian countries and have been used for traditional herbal medicine to treat fever, inflammation, dropsy, gonorrhea and cancer (Park et al, 2010). Although several studies have reported that it has many biological activities (Ryu et al, 2000;Psotová et al, 2003), little is known to regarding its antioxidant properties which is related to these beneficial properties. The purpose of this study was to evaluate the several fractions (n-Hexane, CHCl 3 , n-BuOH, and H 2 O) from 70% EtOH crude extract of Prunella vulgaris var.…”
Section: Introductionmentioning
confidence: 99%